UNIVERSAL REACTIVITY INDICATOR Fix IN EXPERIMENTAL OBSTRUCTIVE JAUNDICE IN MINI-PIGS (Ustozlar uchun, 2026)
The objective is to assess the impact of an immunomodulatory medication during the post-decompression phase and examine the status of non-specific reactivity after biliary decompression in a mini-pig experimental model of obstructive jaundice.Supplies and Procedures: The research, which included 25 lab mini-pigs, was carried out at the RyazSMU WetLab between November 2022 and February 2024. The mice were split into two groups at random and given the immunocorrective medication aminodihydrophthalazindione sodium: a Control Group ($n=12$) and a Comparison Group ($n=13$). There were three phases of the study: